The role of women's economic contribution in the informal sector of the economy : A case study of women in the Mankweng area in Limpopo - Kgoahla, Makholo Seriana (University of Limpopo (Turfloop Campus), 2006)
The study entitled The Role of Women’s Economic Contribution in the informal sector of the economy: A case study of women in Mankweng area in the Limpopo Province focuses on the participation of educated women in the Informal Sector of the economy. The participation of women in the economic development has been found to benefit a lot of families headed by women, Black women in particular. In Mankweng, the study found evidence of increased number of women’s participation in the economic development. This mini-thesis is comprised of four chapters. Chapter 1 This chapter is mainly introduction to the study. The chapter includes the problem statement, motivation for the study, aims and objectives and the importance of the study. The chapter also outlines the methodology of the study, the definition of key concepts used in the study and the limitations of the study. Chapter 2 Chapter 2 comprises the literature background for the study. The literature focuses largely on women in the informal sector, their employment opportunities, marginalization in economic activities and constraints on growth that are faced by women in small business enterprises. The literature also reflects on the challenges and limited achievements of women in their respective trading occupations. Chapter 2 looks at the state of women in the economy. The labour market segment theory attempts to explain gender inequalities in employment on the basis that the labour market is compartmentalized. The chapter also looks at the definition of the informal sector. The division of labour and the informal sector focuses on the areas women concentrate in the labour market. Positioning women in the informal sector and the labour market focuses on the role women play in the informal sector. The last part of the chapter deals with the challenges women are faced with and the opportunities available for them in the informal sector. Chapter 3 Chapter 3 focuses on data analysis and interpretation of the findings of the study. The analysis focuses on the respondents’ personal background and their economic activities as recorded during interviews. Chapter 4 Chapter 4 concludes the study by discussing and presenting a summary of the findings of the study and the implications thereof. A conclusive report is made and recommendations for improving the informal sector and for further research are made.
Thesis (M.Dev.) --University of Limpopo, 2006
Keywords: Women economic contribution; Informal economic sector; 305.420968; Women in economic development; Economic development; Informal sector (economics) -- South Africa; Women -- South Africa